Study of Phase Separation in Liquid-Liquid Systems Using Lix 984n in Organic Phase [Estudio de Separación de Fases en Sistemas Líquido- Líquido Usando Lix 984n en Fase Organic] - Navarro-Donoso, P (Centro Nacional de Investigaciones Metalurgicas, 2012)
In this work we studied the sedimentation and coalescence phenomena in liquid-liquid dispersion without chemical reaction, the aqueous electrolyte consisted of 0.25 M sodium sulfate and an organic phase characteristic organic extractant for copper (LIX 984N) diluted in a commercial solvent (Shellsol 24 AR). The phenomena that dominate the phase separation have been studied by several researchers, which proposed a number of models to predict sedimentation and coalescence profiles. In this work we applied a semi-empirical model to describe the phenomena involved, varying the following experimental conditions: percentage of extractant in organic phase (5 - 30 % v / v), continuous phase (aqueous and organic), time and stirring speed (30 - 1800 s and 400 - 1200 rpm respectively). The main results show that from the 800 rpm of agitation this variable has no influence on primary breakup time, in the same way for 180 seconds of stirring produces the same effect. The fraction of dispersed phase in the packing zone found was 0.74. For higher levels of percentage of extractant in organic phase increased the phase separation time as when the organic phase was used as the continuous phase relative to the aqueous phase. We found a partial adjustment of the experimental data in relation to the simulated values , which is attributable to two factors: the initial inertia of the system once the agitation stopped and the existence of different times of inflection points of the curves of sedimentation and coalescence. In the different articles found in literature assume that the above phenomena occur simultaneously.